Students’ Characters Building In The 2013 English Curriculum And Its Practices In The Classroom: A Case Study - Endang Warniati (STKIP PGRI Nganjuk, 2017)
The aim of the study is to identify the teachers’ perception about the students’ characters building in the 2013 English curriculum and its practices in the classroom at the first grade students in a public Senior High School in Nganjuk regency academic year 2016/2017 which have been using the 2013 English curriculum at the first year.This study is a qualitative case study conducted by involving two English teachers and students at the first grade of that school, academic year 2016/2017. Data of this study mainly obtained through some qualitative techniques, such as curriculum documents analysis, interview, observation, questionnaire, and case reports as well, and analyzed by using comparative method of Glaser and Strauss. Finding of the research are: (1) the English teachers’ perceptions about the students’ characters building as their translation of their knowledge in the 2013 English curriculum are same in general, but they still need to have a precise perception toward the C-2013 and mastering its information better; (2) the English teachers implementation of the 2013 English curriculum in developing the students’ good characters in the teaching learning practices in the classroom are: (a) needs some strategies and creativity to make the students enjoy the lesson, (b) scientific approach recommended as an appropriate approach for the students (c) collaboration learning is highly required in the C-2013 classroom. The finding of the research shows that a good perception of the C-2013 strongly influences to the teaching activity to increase characters building for the students. For that reason the English teachers are expected to extend their knowledge of the C-2013 and have a precise perception as the result of a good understanding in C- 2013 to create more effective, joyful, and meaningful teaching learning process as well to maximize the characters’ value for them.